Speaking - Schofield, James (Tổng hợp, 2014)
Make yourself understood in business This brand new self-study book is the perfect way for business people who spend a lot of time on the phone or in meetings and want to improve their spoken English, getting their message across effectively. The focus is on the key language required to speak English accurately in business.